Cannabinoids for spasticity due to multiple sclerosis or paraplegia: A systematic review and meta-analysis of randomized clinical trials. (October 2017) - da Rovare, Victoria P.; Magalhães, Gabriel P.A.; Jardini, Guilherme D.A.; Beraldo, Matheus L.; Gameiro, Mariel O.; Agarwal, Arnav; Luvizutto, Gustavo José; Paula-Ramos, Lucas; Camargo, Samira Esteves Afonso; de Oliveira, Luciane Dias; Bazan, Rodrigo; El Dib, Regina
Highlights: Spasticity remains prevalent in spinal cord injury and multiple sclerosis. Moderate certainty evidence suggests cannabinoids is associated with a possible decrease in spasticity. However, there was an increase in adverse events such as dizziness and nausea. Trials often had outcomes reported incompletely, inadequate random sequence, and a fail of blinding. Abstract: Objectives: Spasticity remains highly prevalent in patients with spinal cord injury and multiple sclerosis. To summarize the effects of cannabinoids compared with usual care, placebo for spasticity due to multiple sclerosis (MS) or paraplegia. Methods: Searches of MEDLINE, EMBASE, CENTRAL and LILACS to March 2017 were performed to identify randomized controlled trials. The primary outcomes were spasticity and spasm frequency. The criteria were any patient with MS and spasticity affecting upper or lower limbs or both, and that had a confirmed diagnosis of MS based on validated criteria, or however defined by the authors of the included studies. Results: 16 trials including 2597 patients were eligible. Moderate-certainty evidence suggested a non-statistically significant decrease in spasticity (standardized mean difference (SMD) 0.36 [confidential interval (CI) 95% −0.17 to 0.88; p = 0.18; I2 = 88%]), and spasm frequency (SMD 0.04 [CI 95% −0.15 to 0.22]). There was an increase in adverse events such as dizziness (risk ratio (RR) 3.45 [CI 95% 2.71–4.4; p = 0.20; I2 = 23%]), somnolence (RR 2.9 [CI 95% 1.98–4.23; p = 0.77; I2 = 0%]), and nausea (RR 2.25 [CI 95% 1.62–3.13; p = 0.83; I2 = 0%]). Conclusions: There is moderate certainty evidence regarding the impact of cannabinoids in spasticity (average 0.36 more spasticity; 0.17 fewer to 0.88 more) due to multiple sclerosis or paraplegia, and in adverse events such as dizziness (419 more dizziness/1000 over 19 weeks), somnolence (127 more somnolence/1000 over 19 weeks), and nausea (125 more somnolence/1000 over 19 weeks).